Influência da orientação, sombreamento e substrato de ninhos-armadilha na captura de espécies de abelhas e vespas nidificantes em cavidades preexistentes. - Ferreira, Roberta Pereira (2009)
The use of trap nests supplies important biological information about nesting bees and wasps. However, the knowledge about the factors influencing on management of these groups is still scarce. This work aimed to analyze some community structure parameters (species abundance, richness, composition and predominance) in two agricultural areas in the Zona da Mata macro region of Paraiba State: Shading, block material (wood or vermiculite), and tubs opening diameter and cardinal orientation. It was verified the influence of these four factors in the community structure parameters. Both sites where similar in species richness and composition. Alhandra site had an accentuated abundance, due Trypoxylon aurifrons e Centris analis. In shaded area most species where more abundant than in sunny one. Otherwise, in Alhandra site the sunny area had higher species richness. Wood blocks where more expensive and difficult to manufacture. Meanwhile, they had more attractiveness than vermiculite blocks, especially for bees. Number of nests was smaller in predominant wind direction trap nests. The two most abundant species where diameter-generalists. The results and the Trypoxylon aurifrons behavior observed suggest that this species should compete by trap nests holes with bees.